2017
DOI: 10.1080/21642583.2017.1331769
|View full text |Cite
|
Sign up to set email alerts
|

Modulation signal bispectrum analysis of electric signals for the detection and diagnosis of compound faults in induction motors with sensorless drives

Abstract: As a prime driver, induction motor is the most electric energy consuming component in industry. The exposure of the motor to stator winding asymmetry, combined with broken rotor bar fault significantly increases the temperature and reduces the efficiency and life of the motor. Accurate and timely diagnosis of these faults will help to maintain motors operating under optimal status and avoid excessive energy consumption and severe damages to systems. This paper examines the performance of diagnosing the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Equation (2) is altered for modified bispectrum analysis [13], which is used to identify the root cause for oscillations of STHX process. B M (f 1 , f 2 ) E [X(f 2 + f 1 ) X(f 2 -f 1 )X(f 2 )X*(f 2 ) X*(f 2 )] (4)…”
Section: Modified Bispectrum Analysismentioning
confidence: 99%
“…Equation (2) is altered for modified bispectrum analysis [13], which is used to identify the root cause for oscillations of STHX process. B M (f 1 , f 2 ) E [X(f 2 + f 1 ) X(f 2 -f 1 )X(f 2 )X*(f 2 ) X*(f 2 )] (4)…”
Section: Modified Bispectrum Analysismentioning
confidence: 99%
“…20 Extensive research has been conducted to explore the relationship between current and cut force. [20][21][22][23] Kuntog˘lu et al 6 employed seven different sensor types to monitor the cutting area and identified the current sensor as the third most effective in evaluating tool wear. However, utilizing the current sensor for monitoring presents challenges due to the introduction of transmission chain noise, resulting in a low signal-to-noise ratio and signal processing complexities.…”
Section: Introductionmentioning
confidence: 99%
“…Tian et al [5] propose a detector based on bispectrum of modulated signals for bearing fault detection, and can effectively suppress static random noise and discrete aperiodic noise. Shaeboub et al [6] examine the effectiveness of conventional diagnostic features in both motor current and voltage signals using spectrum and modulation signal bispectrum analysis (MSBA), which has a good noise reduction capability. Huang et al [7] use the performance of the conventional bispectrum (CB) method and its new variant, the modulation signal bispectrum (MSB) method to analyze faults from different rotors, and prove that MSB performs significantly better than the CB method.…”
Section: Introductionmentioning
confidence: 99%